Building a Performance Allowance System Merit-Based Pay In The Public Sector - Andi Sutrisno; Muh. Aziz Muslim (Jurnal Indonesia Sosial Teknologi, 2024)
This paper aims to describe how to build a merit pay-based performance allowance system for public organizations using the compensation method. The research method used is qualitative research method with Literature Review. The source of research data used is journal articles from research on merit-based public organizations to measure organizational performance. Researchers focused on taking data from financial policymakers who are daily involved and have a slice of work in the implementation of performance allowance budget distribution. The results of several previous studies showed a positive and significant relationship between the performance-based benefits policy system and employee performance. This study examines conceptually based on research literature on merit pay, which shows that instruments in achievement payments for performance appraisals can motivate employees and increase job satisfaction and increase commitment in organizations. This study provides suggestions that future studies emphasize the need for effective incentive and performance appraisal systems in public administration so as to have an impact on the motivation of public employees which has been carried out.